Development of a gall-resistant stainless-steel hardfacing alloy. (5th April 2018) - Smith, Ryan; Doran, Marc; Gandy, David; Babu, Suresh; Wu, Leonardo; Ramirez, Antonio J.; Anderson, Peter M.
Abstract: This work details the development of a new cobalt-free stainless steel powder metallurgy hardfacing alloy designed to replace Stellite 6, a cobalt-based hardfacing alloy used in nuclear valve applications. The fundamental strategy centers on alloying stainless steels with up to 0.5 wt% nitrogen, which is shown to increase both the volume fraction of hard phase precipitates and the strain-hardening rate of the matrix. The resultant alloy, Nitromaxx, exhibits galling performance that is comparable to Stellite 6, up to 350 ° C. This performance is attributed to the suppression of strain localization events associated with galling. In particular, transmission electron microscopy and diffraction measurements from tensile tests show that the nitrogen addition decreases the calculated matrix stacking fault energy and enhances both deformation-induced martensite transformation at room temperature and deformation twinning at elevated temperature. These strain-hardening mechanisms, coupled with the increase in precipitate volume fraction, effectively suppress localization and enhance galling resistance up to 350 ° C. The enhanced galling resistance cannot be rationalized in terms of tensile stress-strain response alone. Graphical abstract: Highlights: A new wear/gall resistant stainless steel alloy is developed that rivals the performance of Stellite from T = 300 to 625 K; The alloy design strategy is to suppress strain localization hard phases and matrix strain hardening; This is achieved through powder metallurgy and annealing to achieve extraordinarily high nitrogen strengthening; An enhanced strain-induced martensite phase transformation at 298 K and twinning at 625 K are observed.